2019
DOI: 10.1371/journal.pone.0223256
|View full text |Cite
|
Sign up to set email alerts
|

Genomic characterisation of perinatal Western Australian Streptococcus agalactiae isolates

Abstract: As a leading cause of neonatal sepsis, Streptococcus agalactiae, commonly known as Group B Streptococcus, is a major neonatal pathogen. Current global screening practices employ risk- or culture-based protocols for detection of these organisms. In Western Australia (WA), universal culture-based screening is provided, with subsequent intrapartum antibiotic prophylaxis for all S. agalactiae-positive women during labour. Widespread antibiotic exposure is not ideal and this is one of the factors driving developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 67 publications
0
5
1
Order By: Relevance
“…The overrepresentation of ST-1 with asymptomatic carriage [ 5 , 9 , 37 ], as well as the association of ST-1 with serotype V has been well-documented [ 8 , 38 , 39 , 40 , 41 , 42 ]. In contrast to data from Australia [ 43 ], ST-1 is a single dominant ST of serotype V in GBS strains from the US [ 44 ]. Similarly, in our study, CC1 appeared to be largely limited to ST-1, with ST-1 serotype V representing almost two-thirds of all CC1 strains.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…The overrepresentation of ST-1 with asymptomatic carriage [ 5 , 9 , 37 ], as well as the association of ST-1 with serotype V has been well-documented [ 8 , 38 , 39 , 40 , 41 , 42 ]. In contrast to data from Australia [ 43 ], ST-1 is a single dominant ST of serotype V in GBS strains from the US [ 44 ]. Similarly, in our study, CC1 appeared to be largely limited to ST-1, with ST-1 serotype V representing almost two-thirds of all CC1 strains.…”
Section: Discussioncontrasting
confidence: 58%
“…All except one ST-569 strains were isolated from pregnant women. While rarely reported elsewhere [ 38 , 43 , 68 ], ST-569 was the second most predominant ST in Ethiopia [ 69 ]. Moreover, we found one isolate of ST-486 serotype Ia, which according to the public MLST database [ 22 ], has not been detected outside of Africa.…”
Section: Discussionmentioning
confidence: 99%
“…All of the carriage S. agalactiae isolates were serotyped via multiplex assay to detect serotypes Ia, Ib and III [19] and remaining serotypes were determined by standard PCR and gel electrophoresis [20]. In addition to serotyping, 42 of the 246 carriage isolates, 10 of the 10 neonatal invasive isolates and 14 of the 15 reference isolates had whole genome sequence data available [21].…”
Section: Clinical S Agalactiae Host Characteristicsmentioning
confidence: 99%
“…In the present study, we demonstrated A global meningitis genome partnership, with contributions from high, middle and low income countries, has been proposed to aid the WHO defeating meningitis roadmap (63). For GBS, WGS has been central in population surveillance and elucidating the population structure and evolution (15,37,49,64). The publicly available genome sequences and metadata presented here will provide a baseline for monitoring the genomic epidemiology of infant and maternal GBS in Ireland.…”
Section: Discussionmentioning
confidence: 85%